PENDAMPINGAN BRANDING DAN MARKETPLACE UMKM KERIPIK TEMPE DAN PISANG DI DESA NAMPAN KECAMATAN SUKOREJO KABUPATEN PONOROGO - Suyoto Arief; Ramdani Harahap, Soritua Ahmad; Elang Bintang; Aisy, Muwatsiqul; Nur Briyan (Jurnal Al Basirah, 2024)
MSMEs are a source of income for rural communities. Development and management are needed in running MSMEs. MSMEs (Micro, Small and Medium Enterprises) are independent production sectors managed by the private sector or legal entities in all economic sectors, however, there are still a few from the village community who do not understand how to develop and manage MSMEs. Where the MSMEs they have are very feasible and good to be marketed widely, as in one of the communities in Nampan Ponorogo Village, East Java, Mrs. Anna's MSMEs are tempe and banana chips. Therefore, this activity aims to provide assistance and understanding regarding how to develop and manage MSMEs so that these business activities can grow and develop and be able to compete with products in the market today. The method used in community service activities (PkM) by applying "practical learning" which provides technical guidance through direct coaching to partners. The role of the PkM team is to directly assist partners in the Community Service Program (KKN) University of Darussalam Gontor with an activity schedule of almost 1 month. This PkM activity resulted in several assistance in the development and management of MSMEs, including logo making, social media making, halal and P-IRT certification assistance. The development and management of MSMEs have been carried out with several strategies including branding and marketplaces to be able to introduce products to the market with unique packaging and names. With this assistance, it is hoped that it will be able to develop sales levels and consumer confidence with complete halal and P-IRT certification